Association of haplotypes spanning PDZ-GEF2, LOC728637 and ACSL6 with schizophrenia in Han Chinese. Issue 12 (21st August 2008) - Luo, X-j; Diao, H-b; Wang, J-k; Zhang, H; Zhao, Z-m; Su, B
Abstract : Background: Schizophrenia is a complex genetic disorder caused by multiple genetic and environmental factors. Several lines of linkage and association studies have repeatedly suggested that the chromosome 5q22-33 region is implicated in the aetiology of schizophrenia. However, most of the previous studies on the linkage of 5q22–33 with schizophrenia were from European populations, and it was not well characterised in other populations. Methods: We analysed eight single nucleotide polymorphisms (SNPs) located in the 5q23.3 region in a cohort of 506 schizophrenia patients and 672 control subjects from south western China. Single marker association, haplotypic association, sex-specific association and molecular evolutionary analysis were performed. Results: Single marker analysis indicated that SNP5 (rs1355095) in LOC728637 is associated with schizophrenia. When males and females were analysed separately, SNP4 (rs31251) in PDZ-GEF2 is associated with schizophrenia in females. Further analysis using haplotypes demonstrated that a haplotype block spanning PDZ-GEF2, LOC728637 and ACSL6 is highly associated with schizophrenia and several haplotypes in this haploblock have about twofold to 10-fold increase in the affected subjects. In addition, molecular evolutionary analysis suggests that PDZ-GEF2 has undergone adaptive evolution due to Darwinian positive selection in the human lineage. Conclusion: Our data provide evidence of the association of 5q22–33 with schizophrenia in Han Chinese. This chromosomal region is likely responsible for genetic susceptibility to schizophrenia, supporting previous data from European patients. In addition, our evolutionary analysis is consistent with the hypothesis that genes contributing to schizophrenia are likely under positive selection during human evolution.